2021
DOI: 10.1210/endocr/bqab099
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical Thyroid Hormone Receptor α Action Mediates Arterial Vasodilation

Abstract: Background Hypothyroidism impairs cardiovascular health and contributes to endothelial dysfunction with reduced vasodilation. How triiodothyronine (T3) and its receptors are involved in the regulation of vasomotion is not yet fully understood. In general, thyroid hormone receptors (TRs) either influence gene expression (canonical action) or rapidly activate intracellular signaling pathways (noncanonical action). Here we aimed to characterize the T3 action underlying the mechanism of arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…The T3-induced effect was endothelium-dependent, similar to observed in the aorta (Lozano-Cuenca et al, 2016) and skeletal muscle arterioles (Park et al, 1997). The acute action of T3 in endothelial cells is mediated by the cytoplasmic TRα1 receptor and PI3K/Akt signaling cascade with a subsequent eNOS activation and NO production (Colantuoni et al, 2005;Hiroi et al, 2006;Aoki et al, 2015;Lozano-Cuenca et al, 2016;Geist et al, 2021). Presumably, similar mechanisms are involved in the observed endotheliumdependent T3-induced relaxation of rat sural arteries.…”
Section: T3 and T4 Induce Vasorelaxation Of Skeletal Muscle Arteries Via Different Mechanismssupporting
confidence: 67%
See 1 more Smart Citation
“…The T3-induced effect was endothelium-dependent, similar to observed in the aorta (Lozano-Cuenca et al, 2016) and skeletal muscle arterioles (Park et al, 1997). The acute action of T3 in endothelial cells is mediated by the cytoplasmic TRα1 receptor and PI3K/Akt signaling cascade with a subsequent eNOS activation and NO production (Colantuoni et al, 2005;Hiroi et al, 2006;Aoki et al, 2015;Lozano-Cuenca et al, 2016;Geist et al, 2021). Presumably, similar mechanisms are involved in the observed endotheliumdependent T3-induced relaxation of rat sural arteries.…”
Section: T3 and T4 Induce Vasorelaxation Of Skeletal Muscle Arteries Via Different Mechanismssupporting
confidence: 67%
“…Non-genomic effects of TH may be mediated by various receptors including cytoplasmic TRα and TRβ, truncated isoforms of TRα and integrin αvβ3 (Plateroti et al, 2001;Hiroi et al, 2006;Kalyanaraman et al, 2014;Selivanova and Tarasova, 2020;Davis et al, 2021;Geist et al, 2021). TH binding to these receptors could initiate different signaling pathways involving Src-kinase, phosphoinositide-3 kinase (PI3K)/Akt cascade, extracellular signal-regulated protein kinases (ERK1/2) (Cao et al, 2005;Moeller et al, 2005;Lin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed in ex vivo models of vasculature contractility are conflicting: Gachkar and colleagues demonstrated a rapid response to physiologic concentrations of T3, and a decreased response to both hyper-and hypothyroid concentrations, not mediated by AKT, ERK or AMPK (21). More recently, other authors demonstrated an increase in vasodilation following exposure to T3, mediated by PI3K pathway and thyroid hormone receptor alpha (22). Experiments conducted in an animal model of hypothyroidism indicate that exposure to high dose LT3 generates a measurable transcriptional effect within 30' reaching a maximum effect after 6 hours (23).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormones are established regulators of endothelial NO-pathway activity ( McAllister et al, 2005 ; Samuel et al, 2017 ; Selivanova and Tarasova, 2021 ). Endothelial NO-synthase (eNOS) expression and activity are controlled by thyroid hormone receptor α (TRα) ( Hiroi et al, 2006 ; Suarez et al, 2014 ; Geist et al, 2021 ) for which T3 has a greater affinity than T4 ( Schroeder et al, 2014 ). Thuswise, T3 may be considered as a more active regulator of arterial vasomotor responses mediated by eNOS.…”
Section: Introductionmentioning
confidence: 99%